Dredging-induced shell damages to hard clam (Meretrix meretrix): a Malaysian case study - Tan, Kar Soon; Julian Ransangan (2019)
The hard clam (Meretrix meretrix) is a popular edible shellfish in South and Southeast Asia, being heavily exploited by hand dredging in Marudu Bay, Malaysia. The current study was performed to evaluate the shell damages caused by this artisanal dredging gear. Samplings were conducted in triplicates at two sites using both hand dredging and hand collecting (control) sampling methods. The shell length and total weight, damage areas and breakage patterns of each clam were recorded. A questionnaire survey was conducted with local bivalve harvesters to gather information on the fishing pressure in Marudu Bay. Results revealed that the efficiency (fishing yield) of hand dredging gear was three times higher than hand collecting. However, hand dredging gear causes lethal shell damages to small hard clams (<3cm in shell length). Hard clam harvesting is the main occupation of most fishermen in Kg. Popok, but most of them do not comply with the minimum harvesting size established by the fishery department. Moreover, most of the stakeholders are not aware of the negative impacts of hand dredging to the sustainability of the hard clam fishery in Marudu Bay. Therefore, organizing more awareness programs combined with introducing community-based fishery management are highly recommended to promote the sustainability of this artisanal fishery.